Evolution of Indian Satellite meteorological programme - JOSHI, P. C.; NARAYANAN, M. S.; BHATIA, R. C.; MANIKIAM, B.; KIRANKUMAR, A. S.; JAYARAMAN, V. (MAUSAM, 2003)
Recent times have witnessed great strides in weather monitoring and forecasting. One of the key contributors to this development has been space based observations. Space technology has emerged as one of the most fascinating technical achievements and is developing as a powerful tool to study the complex earth-atmosphere system. The space-based observations covering large areas on repetitive basis has been found to be ideal to meet the large observational requirements of weather prediction. Indian programme in satellite meteorology started with Bhaskara satellites in late seventies and the INSAT 1 series in early 80’s and has now graduated into a full-fledged mission contributing significantly to weather and climate services and research. The paper highlights the achievements so far and future plans for advanced missions.